Risk associated with malaria infection in Tihama Qahtan, Aseer region, Kingdom of Saudi Arabia: 2006-2007 - Alshahrani, A; Abdelgader, T; Mohya, M; Jubran, S; Abdoon, A; Daffalla, A; Babiker, A; Kyalo, D; Noor, A; Al-Zahrani, M; Snow, R (OMICS International, 2016)
Introduction: Since 2004, the Kingdom of Saudi Arabia has pursued a policy of malaria elimination. The distribution of malaria at this time was constrained to regions located in the South Western part of the country. The present study aimed to understand the risk of malaria infection and factors associated with these events between March 2006 and August 2007 in one part of Aseer region. Methods: The study was carried out in Tihama Qahtan area in the far southeastern part of Aseer, historically the most malaria endemic area of this region. The area covers 54 villages served by three primary health care centres (Wadi Alhayah, Alfarsha and Albuqaa). Malaria cases were detected using passive case detection (PCD) at the three health centres for 18 months from March 2006, each positive case was investigated using patient and household level enquiries. In addition, four cross-sectional surveys in 12 villages were undertaken using rapid diagnostic tests within the catchments of each health centre coinciding with malaria transmission seasons. Results: Among 1840 individuals examined in the PCD survey, 49 (2.7%) were positive for malaria, most were Plasmodium falciparum cases and one was a P. vivax case. The majority of these infections were likely to have been acquired outside of the area and represent imported cases, including those from the neighboring region of Jazan. Among the 18 locally acquired cases, the majority were adult males who slept outdoors. 3623 individuals were screened during the cross-sectional surveys, 16 (0.44%) were positive and infections only detected during peak, potential transmission periods. Conclusion: There was evidence of local malaria transmission in the Tihama Qahtan area in 2006-2007, however prevalence and incidence of new infections was very low, making the future ambitions of elimination biologically feasible. The constant source of imported infections must be considered in the area’s elimination ambitions, alongside strong behavioural community messages about sleeping outdoors unprotected and travel to malaria endemic areas outside the region.